Validitas Instrumen Tes Berpikir Tingkat Tinggi (HOTS) pada Materi Sistem Respirasi di Kelas XI SMA - Marvia Afrita; Rahmawati Darussyamsu (Universitas Wiralodra, 2020)
Higher order thinking skills is very important in the 2013 curriculum. This 2013 curriculum emphasizes the ability of reasoning for concepts. This ability involves a high cognitive level from Bloom’s taxonomy, C4-C6. One example in improving students HOTS is to develop assessment instruments HOTS. This type research is research and development (R&D) research with using the 4D models. This research develop an assessment instrument in the form of multiple choice. In this research, the object is assessment instrument HOTS on respiration system content. The subject of this research were two lectures major in Biology, Faculty of Mathematics and Natural Sciences UNP. The result of validation show an average value of 87.91 with a valid category. This shows of assessment instrument HOTS on respiration system content is valid among in terms of the feasibility aspects of content, construction, language, and the cognitive level of the assessment instruments is at a HOTS.